Bicuspid Aortic Valve–Associated Regulatory Regions Reveal GATA4 Regulation and Function During Human-Induced Pluripotent Stem Cell–Based Endothelial-Mesenchymal Transition—Brief Report. Issue 2 (15th December 2022) - Huang, Tingting; Cheng, Jiaxi; Feng, Hao; Zhou, Wei; Qiu, Ping; Zhou, Dong; Yang, Dongshan; Zhang, Jifeng; Willer, Cristen; Chen, Y. Eugene; Mizrak, Dogukan; Yang, Bo
Abstract : Background: The endothelial-mesenchymal transition (EndoMT) is a fundamental process for heart valve formation and defects in EndoMT cause aortic valve abnormalities. Our previous genome-wide association study identified multiple variants in a large chromosome 8 segment as significantly associated with bicuspid aortic valve (BAV). The objective of this study is to determine the biological effects of this large noncoding segment in human induced pluripotent stem cell (hiPSC)-based EndoMT. Methods: A large genomic segment enriched for BAV-associated variants was deleted in hiPSCs using 2-step CRISPR/Cas9 editing. To address the effects of the variants on GATA4 expression, we generated CRISPR repression hiPSC lines (CRISPRi) as well as hiPSCs from BAV patients. The resulting hiPSCs were differentiated to mesenchymal/myofibroblast-like cells through cardiovascular-lineage endothelial cells for molecular and cellular analysis. Single-cell RNA sequencing was also performed at different stages of EndoMT induction. Results: The large deletion impaired hiPSC-based EndoMT in multiple biallelic clones compared with their isogenic control. It also reduced GATA4 transcript and protein levels during EndoMT, sparing the other genes nearby the deletion segment. Single-cell trajectory analysis revealed the molecular reprogramming during EndoMT. Putative GATA-binding protein targets during EndoMT were uncovered, including genes implicated in endocardial cushion formation and EndoMT process. Differentiation of cells derived from BAV patients carrying the rs117430032 variant as well as CRISPRi repression of the rs117430032 locus resulted in lower GATA4 expression in a stage-specific manner. TWIST1 was identified as a potential regulator of GATA4 expression, showing specificity to the locus tagged by rs117430032. Conclusions: BAV-associated distal regions regulate GATA4 expression during hiPSC-based EndoMT, which in turn promotes EndoMT progression, implicating its contribution to heart valve development.